Cooperative breeding in the humans: a biosociocultural approach - Rodríguez-Sánchez, Keilyn (2025)
The article offers a hermeneutical bibliographic study of a selection of 73 texts to help better understand the place of cooperative parenting in the evolutionary history of humanity, providing evidence for the bio-social foundation for cooperative and altruistic behavior found among human beings and its selective role in human fitness. The essential role of intergenerational, intra-family, inter-group and intercultural cooperative relationships for human upbringing is evident. From biosociocultural diversity, the theoretical trends associated with the understanding of cooperative behavior in parenting are shown. In addition, the most outstanding authors and the most frequent methods in the study of the variables associated with this cooperative parenting behavior are presented. In this way, it is possible to make visible the process of human upbringing as an essentially social dynamic, where altruistic collaboration has generated a diversity of cultural strategies.